2009
DOI: 10.1073/pnas.0905325106
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively spliced tissue factor induces angiogenesis through integrin ligation

Abstract: The initiator of coagulation, full-length tissue factor (flTF), in complex with factor VIIa, influences angiogenesis through PAR-2. Recently, an alternatively spliced variant of TF (asTF) was discovered, in which part of the TF extracellular domain, the transmembrane, and cytoplasmic domains are replaced by a unique C terminus. Subcutaneous tumors produced by asTF-secreting cells revealed increased angiogenesis, but it remained unclear if and how angiogenesis is regulated by asTF. Here, we show that asTF enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
176
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(196 citation statements)
references
References 25 publications
14
176
0
2
Order By: Relevance
“…Strikingly, murine ECs do not appear to engage β1 integrins while adhering to masTF (Figure 2), yet both β1 and β3 integrins are required for masTFelicited angiogenesis, analogously to the hasTF ( Figure 4) (21). It should be noted that β3-deficient mice exhibit a pathological enhancement of angio genesis rather than inhibition of vessel growth (35); however, aberrations triggered by global β3 deficiency may not be reflective of the effects elicited by soluble β3 ligands (for example, masTF/hasTF) in select tissue subcompartments (for example, the vasculature).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, murine ECs do not appear to engage β1 integrins while adhering to masTF (Figure 2), yet both β1 and β3 integrins are required for masTFelicited angiogenesis, analogously to the hasTF ( Figure 4) (21). It should be noted that β3-deficient mice exhibit a pathological enhancement of angio genesis rather than inhibition of vessel growth (35); however, aberrations triggered by global β3 deficiency may not be reflective of the effects elicited by soluble β3 ligands (for example, masTF/hasTF) in select tissue subcompartments (for example, the vasculature).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that hasTF induces angiogenesis and promotes monocyte-endothelial interactions via integrin ligation, without engaging protease activity (21,22). Thus, hasTF may be of interest in the field of anticancer therapies targeting neovascularization.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to flTF, asTF was demonstrated to mediate cell signaling independently of PAR-2 (10,21,24 ). In 2009, van den Berg and colleagues found that asTF directly binds to ␤3 and ␤1 integrins.…”
Section: Impact Of Tf Isoforms On Signaling In Cancermentioning
confidence: 99%
“…Furthermore, the TF cytoplasmic domain may be directly involved in the expression of vascular endothelial growth factor (VEGF) in tumour cells (53), and TF has been shown to regulate cell migration via interaction with integrin alpha3beta1 and actin-binding protein 280 (54 ,55). In this regard it is noteworthy that alternatively spliced TF is also capable of inducing angiogenesis through ligation of various integrins, conferring additional complexity to the issue (56).…”
Section: How Tf Drives Cancer Progressionmentioning
confidence: 99%